Impacts of targeted advertisements on privacy rights: a meta-analysis study - Alia Ali; Hanan Youssef; Sally Tayie (Insights into Language, Culture and Communication)
The paper explored the changes that digital privacy rights have witnessed in this era in which we live, which has seen a substantial technological boom that has infiltrated individuals’ public and private lives through modern means of communication. To achieve this purpose, the researchers conducted a meta-analysis that included reviewing the previous studies that dealt with the topic and examined the aspects of accordance and differences between them and the most prominent results to be reached. The paper reviewed all studies published during the period from 2020 to2023 that addressed the issues of privacy rights in light of advertisers targeting of them. Restricting only to relevant studies, the total number reached twelve Findings revealed that various factors influence consumers; acceptance to be targeted by personalized online advertising such as privacy concerns, perceived risks, and benefits are the essential aspects of this study. Received: 05 February 2024 Accepted: 25 May 2024 Published: 09 June 2024